Aprendizagem profissional de surdos: superando desafios da comunicação em sala de aula. - Santos, Alice Claudina dos (2020)
In the commercial area, there are still not many studies on the participation of deaf people in professional courses. The belief that circulates in society that perhaps these students are not very productive deserves our attention, as it shows that the inclusive movement so far has not managed to break the barriers that challenge the participation of these young people in the workforce. This research aims to identify the main challenges that may arise in the language used by deaf people in the classroom of a professional education institution. The National Service for Commercial Learning (SENAC), the institution in which the research was carried out, follows the guidelines of the Ministry of Education regarding Linguistic Policies, working, according to bilingualism, the educational option adopted in Brazil, for the education of the deaf. Bilingualism proposes the use of Brazilian Sign Language - Libras (as first language - L1) and Portuguese, preferably written, as second language - L2). In view of the small number of bilingual teachers / instructors, in this context of the classroom, an educational agent appears who must be attuned to the educational proposal, the translator / interpreter of Libras (TILSP), together with the instructor being responsible for the circulation of the knowledge in the classroom. Our reflections will be supported by the studies of: Lacerda and Santos, Fernandes, Leme, among others who claim that there are conditions for Libras and the Portuguese Language, preferably written, to circulate in environments frequented by deaf and listeners; Moura, Cordão and Moraes, Miranda, Viégas, bring the contributions of technical documents from SENAC, in addition to information on professionalization and the world of work.Bardin, Biklen and Bodgan, inspired the methodology used in the research. We opted for a qualitative approach in as we seek to privilege, the understanding of behaviors from the perspective of the ten research participants distributed as follows: two instructors, two translators / interpreters of Libras, two coordinators and four students from two professional education courses. We hope that this research will contribute to improve the acquisition of knowledge in the professional practice of deaf learners in vocational schools.